A multiple separation-of-variables method for 2D consolidation of anisotropic soils under multidirectional drainage constraints and non-uniform loading - Lian-Heng Zhao; Peng-Gen Dai; Qing-Yin Meng; Wei-Ming Wang; San-Feng Liu; Xiang-Hong Ding (European Journal of Environmental and Civil Engineering, 2026)

Nature and timing of W-Sn mineralization in the Xin’anzi Deposit, Nanling Region: constraints from LA-ICP-MS cassiterite U-Pb geochronology and trace element composition - Gen-Wen He; Pei Ni; Wen-Sheng Li; Lin-Lin Peng; Gua-Hua Wang; Xin-Yue Liang; Jia-Hui Yan; Kai-Han Zhang; Li-Na Zhao (Journal of Asian Earth Sciences, 2026)

Novel Streptomyces sp. SCUT-3 promoter’ and 5’UTR chimeras enhanced its alginate lyase expression for kelp degradation - Jun Dai; Hai-Ning Wang; Can Qin; Peng-Bo Dan; Jun-Jin Deng; Lei Wu; Zhi-Wei Li; Fu-Gen Zhang; Chu-Yan Liang; Ming-Shu Zhang; Xiao-Chun Luo (Chemical Engineering Journal, 2026)

Mango peel pectin as a high-ester emulsifier for carotenoid delivery: Structural characterization and application in low-fat ice cream - Teng-Gen Hu; Huan Zhang; Lu Li; Yu-Qing Hu; Jing Wen; Bo Zou; Jian Peng; Li-Na Cheng; Ji-Jun Wu; Geng-Sheng Xiao; Yu-Juan Xu; Yuan-Shan Yu (Carbohydrate Polymers, 2026)

Uplift capacity of suction anchor groups for floating offshore wind turbines: Loading-angle and mooring-position effects - Yancheng Yu; Xuanming Ding; Yu Peng; Jinchuan Wang; Gen Xiong; Ben He; Yiwen Xin (Marine Georesources & Geotechnology, 2026)

A vapor intrusion model incorporating soil stratification and source depletion dynamics - Lian-Heng Zhao; Qiao-Ling Zhang; Xiang-Hong Ding; Peng-Gen Dai; Qing-Yin Meng (Journal of Hazardous Materials, 2026)

Petrogenesis of the Wunugetushan pluton, Inner Mongolia: Implications for porphyry Cu-Mo mineralization - Gen-Yuan Ji; Kui-Feng Mi; Si-Hong Jiang; Hong-Yan Bao; Peng-Cheng Yan (Journal of Asian Earth Sciences, 2026)

Torsional behavior of semi-parallel wire cables under axial tension: An analytical algorithm - Wen-ming Zhang; Yi-chang Cai; Yu-peng Chen; Gen-min Tian; Cheng-ming Peng (Engineering Structures, 2026)

Analytical study of 2D consolidation in anisotropic soils under non-uniform loads and semi-permeable boundaries - Lian-Heng Zhao; Peng-Gen Dai; Qing-Yin Meng; Wei-Ming Wang; San-Feng Liu; Xiang-Hong Ding (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Cellulose nanocrystal-based antimicrobial porous foam loaded with cinnamaldehyde for enhanced chilled meat preservation - Jin-ling Wu; Ai-ling Zhong; Rui Zhang; Hai-yan Huang; Teng-gen Hu; Zhen-lin Xu; Hong Wang; Peng Wen (Food Packaging and Shelf Life, 2026)

Deciphering multi-stage W-Sn mineralization at ore-field scale: new U-Pb geochronology and trace element fingerprinting from the world-class Dayu district, Nanling - Kai-Han Zhang; Pei Ni; Jun-Yi Pan; Yao-Hui Jiang; Guo-Guang Wang; Ming-Sen Fan; Gen-Wen He; Lin-Lin Peng; Zhe Chi; Liang Han; Jun-Ying Ding; Wen-Sheng Li (International Geology Review, 2026)

Dopamine is a key regulator of the sexual receptivity switch in female Nasonia vitripennis - Jian-Qiu Cheng; Yi-Zhen Xu; Zi Wang; Peng-Cheng Liu; Ting Tang; Gen Zhang; Guan-Hong Wang; Hao-Yuan Hu (Animal Behaviour, 2026)

Corrigendum to “All-trans-retinoid acid (ATRA) suppresses chondrogenesis of rat primary hind limb bud mesenchymal cells by downregulating p63 and cartilage-specific molecules” [Environ. Toxicol. Pharmacol. 38(2) (2014) 460–468] - Yun-guo Wang; Peng Xie; Yun-gong Wang; Xue-dong Li; Tao-gen Zhang; Zhao-yong Liu; Quan Hong; Shi-xin Du (Environmental Toxicology and Pharmacology, 2026)

Wolframite and cassiterite geochemistry deciphers W–Sn ore formation: A case study from the Zuoba quartz-vein tungsten deposit, South China - Kai-Han Zhang; Jun-Yi Pan; Pei Ni; Gen-Wen He; Lin-Lin Peng; Ming-Sen Fan; Yuan-Long Zhang; Wen-Sheng Li (Journal of Asian Earth Sciences, 2026)

Machine learning-driven parameter calibration for the FDEM model in weathered rock seabed - Bo Han; Chun-lei Zhang; Gen-qiang Peng; Zhi-shuai Zhang; Yun-long Tie; Bo-nan Zhang (Marine Georesources & Geotechnology, 2026)

Regulation of grain protein content by the amino acid permease gene OsAAP4 in rice - Ming-Xin Li; Feng-Lin Huang; Jin-Hong Lin; Jia-Yi Qu; Guo-Feng Wan; Gen-Cai Song; Jing Zhao; Yan Peng; Zhen-Ning Teng; Ling Liu; Cheng Zheng; Hou-Xiong Wu; et al. (Theoretical and Applied Genetics, 2026)

Three-dimensional hydrodynamic characteristics of the bio-inspired undulating fin under various angular amplitude undulation modes - Ze-Jun Liang; Dong-Yang Chen; Peng Xu; Gen-Jin Dong (Ocean Engineering, 2026)

Snowflake ZIF-8/Cu2S: A novel adsorbent material for efficient capture of radioactive iodine - Shu-Xuan Li; Xuan Zhao; Yi-Ting Chen; Xiao-Jun Dai; Wen-Ge Zhang; Ao-Tian Gu; Peng Wang; Chun-Hui Gong; Ji-Gen Lu; Yi Yang (Journal of Environmental Chemical Engineering, 2025)

Tartary buckwheat-soy protein isolate composite gels: gelling, rheological, water-retention, and texture characteristics at different ratios - Xiao Han; Gen Ma; Lin Wang; Ting Cheng; Yangyang Guo; Liangzhen Jiang; Yan Wan; Xiaoqin Zheng; Changying Liu; Lianxin Peng; Gang Zhao; Xiulan Guo; et al. (Food Hydrocolloids, 2025)

Carbon emission reduction potential of on-demand transit replacing fixed-route transit - Xiao-Fan Wei; Zhe Zhang; Zhong-Ren Peng; Mei-Gen Xue; Hong-Di He (Transportation Research Part D: Transport and Environment, 2025)

Newly discovered cyanobacteria Nostoc sp. PCC7120 for high efficiency biodegradation of thiamethoxam: Photosynthesis response, enzyme strategies, and molecular mechanisms - Shiye Zhu; Jiale Zhang; Anwei Chen; Youzheng Chai; Jianhua Zeng; Gen Lu; Ma Bai; Jihai Shao; Liang Peng; Si Luo (Bioresource Technology, 2025)

Cumulative effects of ocean currents and land-based pollution on the abundance and composition of coastal zooplankton - Liang-gen Wang; Peng-bing Pei; Muhammad Aslam; Tang-cheng Li; Xiao Ke; Xiu-li Yan; Fei-yan Du; Hong Du (Marine Environmental Research, 2025)

Removal performance and mechanism of Bi2O3 for radioactive iodine in water: The role of crystal forms and oxygen vacancy - Xiao-Jun Dai; Yi-Ting Chen; Wen-Ge Zhang; Shu-Xuan Li; Ao-Tian Gu; Chun-Hui Gong; Peng Wang; Ji-Gen Lu; Yi Yang (Chemical Engineering Journal, 2025)

Porcine epidemic diarrhea virus induces mitophagy to inhibit the apoptosis and activation of JAK/STAT1 pathway - Xin Li; Yiwan Wu; Jin Peng; Bingjie Li; XiaoLong Li; Zhibin Yan; Gen Li; Yue Zhang; HongLing He; Jun Luo; Xiaofeng Guo (Veterinary Microbiology, 2025)

Interference between main and auxiliary rotors in floating dual-rotor wind turbines under stationary and surge conditions - Xueying Peng; Lei Duan; Gen Li; Yanhui Jin; Zhaolong Han (Ocean Engineering, 2025)

Monsoon Climate and Anthropogenic Influences Shape Primate Distributions Across the Southeastern Edge of the Qinghai‐Tibet Plateau - Chen Li; Yi‐hao Fang; Guo‐peng Ren; Yan‐peng Li; Zhi‐pang Huang; Liang‐wei Cui; Dionisios Youlatos; Paul A. Garber; Xi‐jun Ni; Hua Zhu; De‐wen Luo; Xin Liu; et al. (Global Change Biology, 2025)
The southeastern edge of the Qinghai‐Tibet Plateau (Yunnan, China) exhibits high biodiversity but stark differences in species richness between its western Longitudinal Range Gorge (LRG) and eastern Yunnan Plateau (YP). We collected distribution data for 16 primate species in Yunnan and analyzed palynological records over the past 20 ka from 21 localities to identify the biogeographic, climatic, and anthropogenic factors that have driven the present‐day distribution of primates in this region. By integrating local ecological knowledge, field surveys, species distribution models, niche utilization rates, and historical vegetation and land use changes, we found that spatial–temporal shifts in the monsoon climate have been a critical factor in shaping primate species richness on the southeastern edge of the Qinghai‐Tibet Plateau. Compared to the YP, the LRG receives more precipitation, has more limited seasonal temperature variation, and has higher minimum temperatures during the coldest month. These conditions have facilitated the development of moist evergreen broadleaf forests, which represent a more suitable habitat for the 14 primate species that inhabit this area. In contrast, the drought‐adapted forests of the YP support only one primate species. Palynological records indicate that the differentiation of the LRG and YP predates human influence. However, over the past 2000 years, anthropogenic habitat loss and hunting have significantly affected the distribution of primates. The ranges of gibbons, langurs, and snub‐nosed monkeys are now restricted to the central and northern regions of the LRG and have disappeared from lower elevations. Lorises have disappeared from their northernmost range. In contrast, the distribution of macaques has remained relatively stable. The Yangtze‐Red River‐24° N line marks the biogeographic boundary of high primate species richness and biodiversity in the LRG and southeastern Yunnan. Our research suggests that changes in monsoon climate have fundamentally shaped contemporary species richness, while recent anthropogenic pressures have caused ‘range contraction’ for many taxa.

Thaw consolidation of two-layer frozen soils considering self-weight: An analytical model - Lian-Heng Zhao; Peng-Gen Dai; Wei-Ming Wang; Qing-Yin Meng; Xiang-Hong Ding (Computers and Geotechnics, 2025)

Metabolomics-based mechanistic insights into antioxidant enhancement in mango juice fermented by various lactic acid bacteria - Shuai Liu; Yu-Jia Peng; Wei-Wei He; Xiao-Xiao Song; Yu-Xin He; Xiao-Yi Hu; Shui-Gen Bian; Yu-Hao Li; Jun-Yi Yin; Shao-Ping Nie; Ming-Yong Xie (Food Chemistry, 2025)

High performance piperidinium based anion exchange membranes with different twisted backbone structures for fuel cells - Ying Jie Liu; Guo Liang Zhang; Yong Qi Hu; Hui Peng; Li Wei Lai; Ai Mei Zhu; Qiu Gen Zhang; Qing Lin Liu (Chemical Engineering Journal, 2025)

Assessing the Interrelationship Between Microplastics and Polychlorinated Biphenyls Contamination in Chinese Mangrove Sediment - Jianqiao He; Jun Deng; Guochao Zhang; Guoqiang Yi; Gen Peng; Yihua Wei; Lu Ren; Yinghui Wang (Journal of Marine Science and Engineering, 2024)
Mangrove ecosystems, critical intertidal zones at the land–ocean interface, are increasingly recognized for their role in microplastic (MP) pollution dynamics. Despite extensive research on the interaction of MPs with various chemical contaminants, the specific contamination levels of polychlorinated biphenyls (PCBs) associated with MPs in mangroves remain poorly understood. In this study, we quantified the concentrations of PCBs on MPs extracted from representative mangrove sediment samples across China, revealing values ranging from 9.80 to 13.91 ng/g. In contrast, PCB concentrations in sediment samples were found to vary between 25.67 and 69.85 ng/g. Our findings indicate a consistent level of PCB contamination on MPs across different sites, although these levels were marginally elevated compared to those in the surrounding sediments. Notably, Penta-PCBs were detected with the highest frequency across all samples analyzed. This study provides crucial insights into the occurrence and distribution of PCBs on MPs within the mangrove ecosystem, highlighting their significance in environmental contamination assessments.

Distinctive patterns of bacterial community succession in the riverine micro-plastisphere in view of biofilm development and ecological niches - Zhen Zhao; Yijin Wang; Yihua Wei; Gen Peng; Tingyu Wei; Jianqiao He; Ruilong Li; Yinghui Wang (Journal of Hazardous Materials, 2024)

Rhizospheric bacterial communities against microplastics (MPs): Novel ecological strategies based on the niche differentiation - Yijin Wang; Zhen Zhao; Meng Jiao; Tiezhu Li; Yihua Wei; Ruilong Li; Gen Peng (Journal of Hazardous Materials, 2024)

Fate and drivers of mariculture-derived microplastics from ponds to mangrove forests - Zhen Zhao; Yihua Wei; Yijin Wang; Gen Peng; Eddy Y. Zeng; Kefu Yu; Xiang-Rong Xu; Ruilong Li (Environmental Pollution, 2024)

Tunable sulfur vacancies in amorphous-crystalline AC-Bi2S3-x@C derived from CAU-17 for efficient capture of radioiodine: Comparison of sulfur vacancies in amorphous and crystalline structures - Kai-Wei Chen; Xin-Yu Zhou; Yi-Ting Chen; Xiao-Jun Dai; Shu-Xuan Li; Ao-Tian Gu; Chun-Hui Gong; Peng Wang; Ping Mao; Ji-Gen Lu; Yi Yang (Chemical Engineering Journal, 2024)

Matrine inhibits invasion and migration of gallbladder cancer via regulating the PI3K/AKT signaling pathway - Rong-Liang Mo; Zhuang Li; Peng Zhang; Ming-Hui Sheng; Gen-Cheng Han; Deng-Qun Sun (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Synergistic structure engineering and electrochemical activation modulating vanadium oxide cathode toward superior zinc-ion storage - Kan Fang; Heng Zhang; Peng Chen; Hua-Yu Zhang; Zhan Wei; Ling Ding; Xiao-Ai Ye; Jiawang Liu; Yi-Lin Liu; Gui-Gen Wang; Hui Ying Yang (Chemical Engineering Journal, 2024)

Three new lanostane-type triterpenes from the epidermis of Wolfiporia cocos - Shi-Tao Wang; Te-Ri-Gen Bao; Peng-Kun Qi; Tao Liu (Natural Product Research, 2024)

The application of freeze-thaw cycle treatment on landfill sludge: Impact on physicochemical properties and physical-mechanical characteristics - Xudong Zhang; Peng Ye; Manabu Fujii; Gen Kondo (Journal of Cleaner Production, 2024)

Spatial allocation of heavy commercial vehicles parking areas through geo-fencing - Jishi Wu; Tao Feng; Peng Jia; Gen Li (Journal of Transport Geography, 2024)

Integrated analysis of transcriptome and small RNAome reveals regulatory network of rapid and long-term response to heat stress in Rhododendron moulmainense - Si-Jia Liu; Chang Cai; Hong-Yue Cai; Yu-Qing Bai; Ding-Yue Wang; Hua Zhang; Jin-Gen Peng; Li-Juan Xie (Planta, 2024)
Main conclusion The post-transcriptional gene regulatory pathway and small RNA pathway play important roles in regulating the rapid and long-term response of Rhododendron moulmainense to high-temperature stress. Abstract The Rhododendron plays an important role in maintaining ecological balance. However, it is difficult to domesticate for use in urban ecosystems due to their strict optimum growth temperature condition, and its evolution and adaptation are little known. Here, we combined transcriptome and small RNAome to reveal the rapid response and long-term adaptability regulation strategies in Rhododendron moulmainense under high-temperature stress. The post-transcriptional gene regulatory pathway plays important roles in stress response, in which the protein folding pathway is rapidly induced at 4 h after heat stress, and alternative splicing plays an important role in regulating gene expression at 7 days after heat stress. The chloroplasts oxidative damage is the main factor inhibiting photosynthesis efficiency. Through WGCNA analysis, we identified gene association patterns and potential key regulatory genes responsible for maintaining the ROS steady-state under heat stress. Finally, we found that the sRNA synthesis pathway is induced under heat stress. Combined with small RNAome, we found that more miRNAs are significantly changed under long-term heat stress. Furthermore, MYBs might play a central role in target gene interaction network of differentially expressed miRNAs in R. moulmainense under heat stress. MYBs are closely related to ABA, consistently, ABA synthesis and signaling pathways are significantly inhibited, and the change in stomatal aperture is not obvious under heat stress. Taken together, we gained valuable insights into the transplantation and long-term conservation domestication of Rhododendron , and provide genetic resources for genetic modification and molecular breeding to improve heat resistance in Rhododendron .

Secreted salt and hydrodynamic factors combine to affect dynamic fluctuations of microplastics on mangrove leaves - Yihua Wei; Meng Jiao; Zhen Zhao; Liangdong Tang; Yijin Wang; Jun Deng; Gen Peng; Ruilong Li; Yinghui Wang (Journal of Hazardous Materials, 2024)

Influence of meteorological factors on open biomass burning at a background site in Northeast China - Yulong Wang; Linlin Liang; Wanyun Xu; Chang Liu; Hongbing Cheng; Yusi Liu; Gen Zhang; Xiaobin Xu; Dajiang Yu; Peng Wang; Qingli Song; Jiumeng Liu; et al. (Journal of Environmental Sciences, 2024)

Deciphering the biotic and abiotic drivers of coalescence asymmetry between soil and manure microbiomes - Chunkai Li; Xianping Li; Sana Romdhane; Yanhong Cheng; Gen Li; Rui Cao; Peng Li; Jingjing Xu; Yexin Zhao; Yang Yang; Jiaguo Jiao; Feng Hu; et al. (Science of The Total Environment, 2024)

Observational insights into the environmental effect for secondary inorganic aerosol formation in the Northeast China: Influence of biomass burning - Yulong Wang; Linlin Liang; Wanyun Xu; Chang Liu; Hongbing Cheng; Yusi Liu; Gen Zhang; Xiaobin Xu; Dajiang Yu; Peng Wang; Qingli Song; Jiumeng Liu; et al. (Atmospheric Research, 2024)

Yellow pigments produced by oxidative oligomerization of dihydrochalcone glucoside and the reaction mechanism - Zhang-Bin Liu; Yosuke Matsuo; Yoshinori Saito; Yong-Lin Huang; Dian-Peng Li; Gen-ichiro Nonaka; Takashi Tanaka (Food Chemistry, 2023)

High-performance Cu/Mn modified ceramsite as a persulfate activator to degrade oxytetracycline in batch Erlenmeyer flask and continuous-flow fixed-bed column systems: An exploration of its practicability and non-radical mechanisms - Huang-gen Yang; Mang Lu; Xue-jiao Wu; Rui-ting Dong; Tao-peng Luo; Hui-hua Zhong (Chemosphere, 2023)

Selective enrichments for color microplastics loading of marine lipophilic phycotoxins - Ruilong Li; Jiuming Wang; Jun Deng; Gen Peng; Yijin Wang; Tiezhu Li; Beibei Liu; Yong Zhang (Journal of Hazardous Materials, 2023)

Synthesis of novel magnetic pitch-based hypercrosslinked polymers as adsorbents for effective recovery of Ag+ with high selectivity - Qi Peng; Hongwei Zhao; Guang Chen; Qilin Yang; Xinxiu Cao; Shaohui Xiong; Anguo Xiao; Gen Li; Bo Liu; Qingquan Liu (Journal of Environmental Management, 2023)

Global-scale no-tillage impacts on soil aggregates and associated carbon and nitrogen concentrations in croplands: A meta-analysis - Peng Li; Duo Ying; Jing Li; Jianjun Deng; Chunkai Li; Shanyi Tian; Gen Zhao; Choufei Wu; Jiaguo Jiao; Min Jiang; Feng Hu (Science of The Total Environment, 2023)

Protective effects of egg yolk immunoglobulins (IgY) against CyHV-2 infection in gibel carp (Carassius gibelio) - Bing-Yao Sun; Hai-Yan Kou; Pan-Yang Jian; Ling-Jiao Kong; Jie Fang; Peng-Kun Meng; Kang Wu; Cai-Gen Yang; Gang Yang; Xue-Hong Song (Aquaculture, 2023)

A novel photochemical conversion technique for reliable calibration of peroxyacetyl nitrate (PAN) analyzers - Xiaowei He; Chenglong Zhang; Pengfei Liu; Gen Zhang; Hai Wu; Yuexiang Peng; Junfeng Liu; Chengtang Liu; Yujing Mu (Science of The Total Environment, 2023)

Intelligent shielding material based on VO2 with tunable near-field and far-field electromagnetic response - Si-Yuan Liao; Xiao-Yun Wang; Hai-Peng Huang; Yu-Ying Shi; Qiao-Feng Wang; You-Gen Hu; Peng-Li Zhu; Rong Sun; Ching-Ping Wong; Yan-Jun Wan (Chemical Engineering Journal, 2023)

46,XY disorders of sex development: the use of NGS for prevalent variants - Qi-Gen Xie; Peng Luo; Kai Xia; Zuo-Qing Li; Zhe Xu; Cheng Su; Chun-Hua Deng (Human Genetics, 2022)

Orexin A peptidergic system: comparative sleep behavior, morphology and population in brains between wild type and Alzheimer’s disease mice - Peng Zhao; Yaqian You; Zhe Wang; Yanjun Zhou; Gaoshang Chai; Gen Yan; Zhewu Jin; Qing Wang; Hongxu Sun (Brain Structure and Function, 2022)
Sleep disturbance is common in patients with Alzheimer’s disease (AD), and orexin A is a pivotal neurotransmitter for bidirectionally regulating the amyloid-β (Aβ) deposition of AD brain and poor sleep. In the present study, we examined the characteristic of sleep–wake architecture in APPswe/PSldE9 (APP/PS1) and Aβ-treated mice using electroencephalogram (EEG) and electromyographic (EMG) analysis. We compared the expression of orexin A, distribution, and morphology of the corresponding orexin A-positive neurons using innovative methods including three-dimensional reconstruction and brain tissue clearing between wild type (WT) and APP/PS1 mice. Results from our study demonstrated that increased wakefulness and reduced NREM sleep were seen in APP/PS1 and Aβ treated mice, while the expression of orexin A was significantly upregulated. Higher density and distribution of orexin A-positive neurons were seen in APP/PS1 mice, with a location of 1.06 mm–2.30 mm away from the anterior fontanelle compared to 1.34 mm–2.18 mm away from the anterior fontanelle in WT mice. These results suggested that the population and distribution of orexin A may play an important role in the progression of AD.

Linking hydraulic geometry, land use, and stream water quality in the Taihu Basin, China - Yaoyi Liu; Hongju Zhang; Peng Zeng; Yukun Wang; Gen Li; Fengyun Sun; Yue Che (Environmental Monitoring and Assessment, 2021)

First report of tobacco rattle virus in hydrangea in China - Zhao-Lin Ji; Peng-Xiang Zhu; Gen-He He; Yong-Hui Liao; Feng Zhu (Journal of Plant Pathology, 2020)

Design, synthesis and antifungal activities of novel pyrrole- and pyrazole-substituted coumarin derivatives - Shu-Guang Zhang; Chao-Gen Liang; Yue-Qing Sun; Peng Teng; Jia-Qun Wang; Wei-Hua Zhang (Molecular Diversity, 2019)

A new Em-like protein from Lactuca sativa, LsEm1, enhances drought and salt stress tolerance in Escherichia coli and rice - Dian-Jun Xiang; Li-Li Man; Chun-Lan Zhang; Peng-Liu; Zhi-Gang Li; Gen-Chang Zheng (Protoplasma, 2018)

Avian influenza viruses (AIVs) H9N2 are in the course of reassorting into novel AIVs - Hui-ping Chang; Li Peng; Liang Chen; Lu-fang Jiang; Zhi-jie Zhang; Cheng-long Xiong; Gen-ming Zhao; Yue Chen; Qing-wu Jiang (Journal of Zhejiang University-SCIENCE B, 2018)

QTL Mapping for Resistance to Iridovirus in Asian Seabass Using Genotyping-by-Sequencing - Le Wang; Bin Bai; Shuqing Huang; Peng Liu; Zi Yi Wan; Baoqing Ye; Jinlu Wu; Gen Hua Yue (Marine Biotechnology, 2017)

Genome-Wide Association Study Identifies Loci Associated with Resistance to Viral Nervous Necrosis Disease in Asian Seabass - Le Wang; Peng Liu; Shuqing Huang; Baoqing Ye; Elaine Chua; Zi Yi Wan; Gen Hua Yue (Marine Biotechnology, 2017)

Relationship between leaf reddening, ROS and antioxidants in Buxus microphylla during overwintering - Xue-ru Jiang; Jin-gen Peng; Meng-xue Jia; Yan Liu; Ling Guo; Rong-fu Gao (Acta Physiologiae Plantarum, 2016)

Mapping QTL for Resistance Against Viral Nervous Necrosis Disease in Asian Seabass - Peng Liu; Le Wang; Zi Yi Wan; Bao Qing Ye; Shuqing Huang; Sek-Man Wong; Gen Hua Yue (Marine Biotechnology, 2016)

Immunotherapy of DC-CIK cells enhances the efficacy of chemotherapy for solid cancer: a meta-analysis of randomized controlled trials in Chinese patients - Xiao-peng Lan; You-gen Chen; Zheng Wang; Chuan-wei Yuan; Gang-gang Wang; Guo-liang Lu; Shao-wei Mao; Xun-bo Jin; Qing-hua Xia (Journal of Zhejiang University-SCIENCE B, 2015)

Genome-wide discovery of gene-related SNPs in Barramundi Lates calcarifer - Le Wang; Shu Qing Huang; Jun Hong Xia; Peng Liu; Zi Yi Wan; Gen Hua Yue (Conservation Genetics Resources, 2015)

Patients with type 2 diabetes exhibit cognitive impairment with changes of metabolite concentration in the left hippocampus - Yue Wang; Xiao-yun Xu; Chun-hua Feng; Yuan-ling Li; Xia Ge; Gen-lin Zong; Yi-bin Wang; Bo Feng; Peng Zhang (Metabolic Brain Disease, 2015)

Diosmetin inhibits the expression of alpha-hemolysin in Staphylococcus aureus - Shui Liu; Xuan Zhou; Wenhua Li; Hong Zhang; Bing Zhang; Gen Li; Bowen Liu; Xuming Deng; Liping Peng (Antonie van Leeuwenhoek, 2015)

Mapping Quantitative Trait Loci for Omega-3 Fatty Acids in Asian Seabass - Jun Hong Xia; Grace Lin; Xiaoping He; Bu Yunping; Peng Liu; Feng Liu; Fei Sun; Rongjian Tu; Gen Hua Yue (Marine Biotechnology, 2014)

Warnstorfia exannulata, an aquatic moss in the Arctic: seasonal growth responses - Cai-Qing Guo; Ryszard Ochyra; Peng-Cheng Wu; Rodney D. Seppelt; Yi-Feng Yao; Lin-Gen Bian; Su-Ping Li; Cheng-Sen Li (Climatic Change, 2013)

The effects of molybdenum and boron on the rhizosphere microorganisms and soil enzyme activities of soybean - Ting Sun; Yue P. Wang; Zhi Y. Wang; Peng Liu; Gen D. Xu (Acta Physiologiae Plantarum, 2013)

A transgenic Bm cell line of piggyBac transposon-derived targeting expression of humanized glycoproteins through N-glycosylation - Jia-biao Hu; Peng Zhang; Mei-xian Wang; Fang Zhou; Yan-shan Niu; Yun-gen Miao (Molecular Biology Reports, 2012)

Timing, Conditions, and Complications of Post-operative Conception and Pregnancy in Female Renal Transplant Recipients - Long-gen Xu; Shu Han; Yong Liu; Hong-wei Wang; Yi-rong Yang; Feng Qiu; Wan-ling Peng; Li-gong Tang (Cell Biochemistry and Biophysics, 2011)

Expression of Trichoderma viride endoglucanase III in the larvae of silkworm, Bombyx mori L. and characteristic analysis of the recombinant protein - Xing-hua Li; Peng Zhang; Mei-xian Wang; Fang Zhou; Firdose Ahmad Malik; Hua-jun Yang; Roy Bhaskar; Jia-biao Hu; Chun-guang Sun; Yun-gen Miao (Molecular Biology Reports, 2011)

Morphological and physiological responses of root tip cells to Fe2+ toxicity in rice - Yi Zhang; Guo Hong Zheng; Peng Liu; Jin Min Song; Gen Di Xu; Miao Zhen Cai (Acta Physiologiae Plantarum, 2011)

Effects of temperature change on water discharge, and sediment and nutrient loading in the lower Pearl River basin based on SWAT modelling - Ying Li; Bao-Ming Chen; Zhong-Gen Wang; Shao-Lin Peng (Hydrological Sciences Journal, 2011)

Determinants of the geographical extent of invasive plants in China: effects of biogeographical origin, life cycle and time since introduction - Qiao Q. Huang; Chen Qian; Yu Wang; Xin Jia; Xin F. Dai; Hao Zhang; Fei He; Shao L. Peng; Gen X. Wang (Biodiversity and Conservation, 2010)

Role of desert annuals in nutrient flow in arid area of Northwestern China: a nutrient reservoir and provider - Bao-Ming Chen; Gen-Xuan Wang; Shao-Lin Peng (Plant Ecology, 2009)

Developmental characteristics and response to iron toxicity of root border cells in rice seedlings - Cheng-hua Xing; Mei-hong Zhu; Miao-zhen Cai; Peng Liu; Gen-di Xu; Shao-hui Wu (Journal of Zhejiang University-SCIENCE B, 2008)